Circulatory disease in French nuclear fuel cycle workers chronically exposed to uranium: a nested case–control study. Issue 4 (31st October 2017) - Zhivin, Sergey; Guseva Canu, Irina; Davesne, Estelle; Blanchardon, Eric; Garsi, Jérôme-Philippe; Samson, Eric; Niogret, Christine; Zablotska, Lydia B; Laurier, Dominique
Abstract : Objectives: There is growing evidence of an association between low-dose external γ-radiation and circulatory system diseases (CSDs), yet sparse data exist about an association with chronic internal uranium exposure and the role of non-radiation risk factors. We conducted a nested case–control study of French AREVA NC Pierrelatte nuclear workers employed between 1960 and 2005 to estimate CSD risks adjusting for major CSD risk factors (smoking, blood pressure, body mass index, total cholesterol and glycaemia) and external γ-radiation dose. Methods: The study included 102 cases of death from CSD and 416 controls individually matched on age, gender, birth cohort and socio-professional status. Information on CSD risk factors was collected from occupational medical records. Organ-specific absorbed doses were estimated using biomonitoring data, taking into account exposure regime and uranium physicochemical properties. External γ-radiation was measured by individual dosimeter badges. Analysis was conducted with conditional logistic regression. Results: Workers were exposed to very low radiation doses (mean γ-radiation dose 2 and lung uranium dose 1 mGy). A positive but imprecise association was observed (excess OR per mGy 0.2, 95% CI 0.004 to 0.5). Results obtained after adjustment suggest that uranium exposure might be an independent CSD risk factor. Conclusions: Our results suggest that a positive association might exist between internal uranium exposure and CSD mortality, not confounded by CSD risk factors. Future work should focus on numerous uncertainties associated with internal uranium dose estimation and on understanding biological pathway of CSD after protracted low-dose internal radiation exposure.